Pediatric Palliative Care Initiative in Cambodia - Çeliker, Mahmut Yaşar; Pagnarith, Yos; Akao, Kazumi; Sophearin, Dim; Sorn, Sokchea (Frontiers in Public Health, 2017)
Cancer care with curative intent remains unattainable in many resource-limited settings such as Cambodia. Cambodia has a small workforce with limited financial and healthcare resources resulting in delayed diagnoses and limited diagnostic and therapeutic tools. Thus, palliative care becomes the primary form of care in most cases. Although palliative care is becoming an integral part of medical care in developed countries, this concept remains poorly understood and utilized in developing countries. Angkor Hospital for Children serves a relatively large pediatric population in northern Cambodia. According to the modern definition of palliative care approximately 2/3 of the patients admitted to the hospital were deemed candidates to receive palliative care. In an effort to develop a pediatric palliative care team utilizing existing resources and intensive training, our focus group recruited already existing teams of different health care foci and other motivated members of the hospital. During this process, we have also formed a palliative care training team of local experts to maintain ongoing palliative care education. Feedback from the patients and health care providers confirmed the effectiveness of these efforts. In conclusion, palliative and sustainable care was offered effectively in a resource-limited setting with adequately trained and motivated local providers. In this article, the steps and systems used to overcome challenges in Cambodia are summarized in the hope that our experience urges governmental and non-governmental agencies to support similar initiatives.